The onset of neoglaciation in Iceland and the 4.2 ka event - Á. Geirsdóttir; G. H. Miller; G. H. Miller; J. T. Andrews; D. J. Harning; D. J. Harning; L. S. Anderson; L. S. Anderson; C. Florian; D. J. Larsen; T. Thordarson (Climate of the Past, 2019)
Strong similarities in Holocene climate reconstructions derived from multiple proxies (BSi, TOC – total organic carbon, δ13C, C∕N, MS – magnetic susceptibility, δ15N) preserved in sediments from both glacial and non-glacial lakes across Iceland indicate a relatively warm early to mid Holocene from 10 to 6 ka, overprinted with cold excursions presumably related to meltwater impact on North Atlantic circulation until 7.9 ka. Sediment in lakes from glacial catchments indicates their catchments were ice-free during this interval. Statistical treatment of the high-resolution multi-proxy paleoclimate lake records shows that despite great variability in catchment characteristics, the sediment records document more or less synchronous abrupt, cold departures as opposed to the smoothly decreasing trend in Northern Hemisphere summer insolation. Although all lake records document a decline in summer temperature through the Holocene consistent with the regular decline in summer insolation, the onset of significant summer cooling occurs ∼5 ka at high-elevation interior sites but is variably later at sites closer to the coast, suggesting that proximity to the sea may modulate the impact from decreasing summer insolation. The timing of glacier inception during the mid Holocene is determined by the descent of the equilibrium line altitude (ELA), which is dominated by the evolution of summer temperature as summer insolation declined as well as changes in sea surface temperature for coastal glacial systems. The glacial response to the ELA decline is also highly dependent on the local topography. The initial ∼5 ka nucleation of Langjökull in the highlands of Iceland defines the onset of neoglaciation in Iceland. Subsequently, a stepwise expansion of both Langjökull and northeast Vatnajökull occurred between 4.5 and 4.0 ka, with a second abrupt expansion ∼3 ka. Due to its coastal setting and lower topographic threshold, the initial appearance of Drangajökull in the NW of Iceland was delayed until ∼2.3 ka. All lake records reflect abrupt summer temperature and catchment disturbance at ∼4.5 ka, statistically indistinguishable from the global 4.2 ka event, and a second widespread abrupt disturbance at 3.0 ka, similar to the stepwise expansion of Langjökull and northeast Vatnajökull. Both are intervals characterized by large explosive volcanism and tephra distribution in Iceland resulting in intensified local soil erosion. The most widespread increase in glacier advance, landscape instability, and soil erosion occurred shortly after 2 ka, likely due to a complex combination of increased impact from volcanic tephra deposition, cooling climate, and increased sea ice off the coast of Iceland. All lake records indicate a strong decline in temperature ∼1.5 ka, which culminated during the Little Ice Age (1250–1850 CE) when the glaciers reached their maximum Holocene dimensions.